Hearing and feeling the music in every step: Musical walks and biographical experience of lockdown. Issue 1 (April 2023) - Nurse, Lyudmila; Robertson, Chika
The article investigates the ways in which young musicians explored new (unfamiliar) social landscapes and emotions during Covid-19 pandemic lockdowns, through learning to listen to the "music within their steps" while walking on their own or with members of their own families for the inter-disciplinary project 'The Musical Steps'. The project examines the self-recorded essays, visual materials and reflections by the young musicians and their parents, which reveal new cultural perspectives of sound, space and silence, along with the thoughts about musical repertoire which were inspired by the walks. Methodologically, we applied the walking biographical method that enabled us to explore young musicians' reflections on music and their lives during lockdowns from an inter-disciplinary perspective. The walking biographies approach to research on the move has been specially adapted for young musicians and their families by the authors. This article explores how walking changed young musicians' emotional perceptions of music and what they heard and felt during and after their walks. Questions were raised as to whether the walks affected their physical and mental well-being, both personally and musically, and whether the walks influenced their understanding of their cultural background/origin.